Photographed at Razliv Station with a wig and without his beard for a forged passport. Compare: BG A8/380 and 69/39 A, page 46 - Leščenko, D.I.
Photographed at Razliv Station with a wig and without his beard for a forged passport. Compare: BG A8/380 and 69/39 A, page 46.